2020
DOI: 10.1038/s41598-020-73249-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PI3K inhibition on the radiotherapy response of head and neck cancer cells

Abstract: Radiotherapy has a central role in the treatment of head and neck squamous cell carcinoma (HNSCC). Activation of the PI3K/AKT/mTOR pathway can decrease the efficiency of radiotherapy via the promotion of cell survival and DNA repair. Here, the influence of PI3K pathway inhibition on radiotherapy response was investigated. Two PI3K inhibitors were investigated and both BKM120 and GDC0980 effectively inhibited cellular and clonogenic growth in 6 HNSCC cells, both HPV-positive as well as HPV-negative. Despite tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Aberrant upregulation and activation of PI3K/AKT/mTOR pathway is also correlated with resistance radiotherapy. A number of preclinical studies indicated that inhibition of PI3K/AKT/mTOR pathway can sensitize different types of cancer cells, including non-small cell lung cancer, breast cancer, nasopharyngeal carcinoma, oral squamous, and head and neck cancer, to radiotherapy ( Yu et al, 2017 ; Chen et al, 2020b ; Chen et al, 2020c ; Glorieux et al, 2020 ; Schötz et al, 2020 ; Wanigasooriya et al, 2020 ). In breast cancer, IL-6 pre-treatment followed by SIRT1 activation by SRT1720 combined with dual PI3K/mTOR inhibitor NVP-BEZ235 obviously increased sensitivity of the cancer stem cells to radiation, so that late stage breast cancer cells therapeutic effect was effectively improved ( Fatehi et al, 2018 ; Masoumi et al, 2020 ).…”
Section: Pi3k/akt/mtor Pathway Induces Drug Resistance In Breast Cancmentioning
confidence: 99%
“…Aberrant upregulation and activation of PI3K/AKT/mTOR pathway is also correlated with resistance radiotherapy. A number of preclinical studies indicated that inhibition of PI3K/AKT/mTOR pathway can sensitize different types of cancer cells, including non-small cell lung cancer, breast cancer, nasopharyngeal carcinoma, oral squamous, and head and neck cancer, to radiotherapy ( Yu et al, 2017 ; Chen et al, 2020b ; Chen et al, 2020c ; Glorieux et al, 2020 ; Schötz et al, 2020 ; Wanigasooriya et al, 2020 ). In breast cancer, IL-6 pre-treatment followed by SIRT1 activation by SRT1720 combined with dual PI3K/mTOR inhibitor NVP-BEZ235 obviously increased sensitivity of the cancer stem cells to radiation, so that late stage breast cancer cells therapeutic effect was effectively improved ( Fatehi et al, 2018 ; Masoumi et al, 2020 ).…”
Section: Pi3k/akt/mtor Pathway Induces Drug Resistance In Breast Cancmentioning
confidence: 99%
“…The PI3K pathway limits the effect of RT and chemotherapies by promoting cell survival and DNA repair, and thus PI3K inhibitors could, in principle, potentiate the effect of such therapies. A number of emerging studies, both pre-clinical and clinical, indicate that this may be the case for some PI3K inhibitors in combination with cisplatin and radiotherapy (27,(57)(58)(59)(60)(61).…”
Section: Rtks As Targetsmentioning
confidence: 99%
“…When combined with radiation, BEZ235 was also found to result in strongly enhanced radiosensitivity [31][32][33][34][35][36]. In contrast, for other PI3K-inhibitors such as BKM120 and GDC0980, no such enhancement was obtained [37].…”
Section: Introductionmentioning
confidence: 97%